Utilization of Devices as Learning Media in Increasing Student Achievement During The Covid-19 Pandemic - Jajang Hendar Hendrawan; Arnie Fajar; Imas Kartika (Social Studies Conference Proceedings, 2022)
Learning during the Covid-19 pandemic can be done remotely, so teachers are required to be able to use information and communication technology-based learning, one of which is by using gadgets. Students can study anytime and anywhere. The problem in this research is how to use gadgets as learning media to improve student achievement. Qualitative research approach with case study method at SDN Budikarya. The study results: using gadgets as media and assessing learning outcomes has been going well. Student learning achievement has increased. The supporting factor for the success of distance learning is the independent ownership of the device from the students, while the inhibiting factor is the time that students spend playing is far greater than the time for studying. This device should be balanced with the use of the school LMS to integrate all data. Teachers and parents should check students' devices regularly.